Contemporary Islamic Discourse between Rationality and Sanctification - Abdel Kadder Naffati; Fuat Hasanudin (Direktorat Pondok Pesntren Universitas Islam Indonesia, 2022)
The discourse on contemporary Islam is divided into two modes of thought, one aims to read texts based on reason, insight, criticism and reality, and the second aims to sanctify the text through traditional understanding, ijtihad and minimizing the addition of new methods in the context of interpretation. Researchers in this paper will discuss contemporary Islamic discourse from both perspectives and offer a two-pronged approach to the development of contemporary Islamic discourse. The paper argues that it is necessary in contemporary Islamic discourse to combine the two approaches so that they can be used together without negating the other. A sanctifying approach is necessary for certain contexts to preserve the sacred and not eliminate the symbol of sacredness. The rationalization approach does not mean excessive interpretation so that it falls into the category of blameworthy ta'wil, rather its purpose is to objectively generate knowledge. Keywords: Contemporary Islamic Discourse, Rationality, Sanctification